Faroese skjaldur - Leonard, Stephen Pax (World Oral Literature Project, 2010)
Dr Leonard is a Research Fellow at Trinity Hall College, the Department of Linguistics and the Scott Polar Research Institute, all at the University of Cambridge. He is an anthropological linguist with research interests in the role of language in the establishment of social and linguistic identities in small speech communities, the ethnography of speaking, endangered languages and cultures, linguistic diversity and language revitalisation. His doctoral research at the University of Oxford focused on the construction of social and linguistic identity in early Iceland, and he has conducted sociolinguistic and ethnographic research in Iceland and the Faroe Islands. In 2010, Dr Leonard embarked on a new project to document the endangered oral traditions and communicative practices of the Inughuit people in northwest Greenland. Faroese skjaldur are a genre of oral literature and music comprising rhymes, lullabies and short tales that have existed for centuries and played a part in the transmission — and survival — of the Faroese language. Rich in content, skjaldur illustrate how folklore, language and local knowledge were passed down the generations.While the origins of the genre remain opaque, they were part of a wider tradition of oral literature that included ballads, kvæ ir (poems, tales) and tættir (satirical ballads, often rude and insulting). The nineteenth century, when the Faroese language was most threatened by the colonial language, Danish, saw the flourishing of verbal arts, ethnic music and ballads.The influence of skjaldur and other forms of oral literature on the vernacular language has been disproportionately significant, as Faroese did not develop a written tradition until the nineteenth century. Faroese was never a minority language as such and survived the onslaught of Danish through its position as an oral form in a bilingual environment, with its use restricted to the homestead where oral literature continued to thrive. The contribution of skjaldur to the development of the Faroese language is ...